Examining the Relationship between Income Inequality and Growth from the Perspective of EU Member States' Stage of Development - Ionuț Jianu; Marin Dinu; Dragoș Huru; Alexandru Bodislav (Sustainability, 2021)
In this paper, we examined the relationship between income inequality and economic growth from the perspective of each country's level of development in the European Union, this linkage being reviewed using the median of GDP per capita expressed in the purchasing power standard to split the European Union Member States into two clusters of 14 countries each. Furthermore, we estimated the impact of income inequality on economic growth during the 2010-2018 period at the level of both clusters using the Estimated Generalized Least Squares with a fixed effects method, reinforced by the cross-section weights option. Our results show that income inequality is positively linked to economic growth in the case of developed EU Member States, while for developing EU countries, income inequality is detrimental to growth. This also demonstrates that income gaps may have positive and negative effects on growth depending on the stage of development, this providing important evidence for the need to promote an optimum level of income inequality.
Keywords: O11; D63; 330; income inequality; economic growth; development; European Union; Panel